Stance Accounts of Political and Religious Identities in ‘Tuku’ Music - Jakaza, Ernest; Mangeya, Hugh (Palgrave Macmillan, Cham, 2022)
Music has become one of the most powerful tools to communicate diverse issues in the public discourse of contemporary societies. Political and religious identities are among a plethora of constructions and contestations of meanings advanced by music producers and artists. The textuality of songs is not neutral, but a matter of a public act that dialogically positions and (dis)aligns subjects with certain political and religious identities. It is in this context that this chapter evaluates political and religious identities in Oliver Mtukudzi’s music. It argues that Mtukudzi dialogically constructed and contested certain political and religious identities, taking a stance toward the self and others in response to salient dimensions of the socio-cultural situation. We engage the Stance theory to make an assessment of how Mtukudzi expressed his feelings, judgments and commitments in the construction of political and religious identities in his songs. Mtukudzi’s political and religious songs are conveniently sampled. Political and religious discourse identities in Tuku’s music are niche areas that have not been explored from a discourse-linguistic perspective.